Can Working Memory and Inhibitory Control Predict Second Language Learning in the Classroom?. (1st October 2015) - Linck, Jared A.; Weiss, Daniel J.
The role of executive functioning in second language (L2) aptitude remains unclear. Whereas some studies report a relationship between working memory (WM) and L2 learning, others have argued against this association. Similarly, being bilingual appears to benefit inhibitory control, and individual differences in inhibitory control are related to online L2 processing. The current longitudinal study examines whether these two components of executive functioning predict learning gains in an L2 classroom context using a pretest/posttest design. We assessed 25 university students in language courses, who completed measures of WM and inhibitory control. They also completed a proficiency measure at the beginning and end of a semester and reported their grade point average (GPA). WM was positively related to L2 proficiency and learning, but inhibitory control was not. These results support the notion that WM is an important component of L2 aptitude, particularly for predicting the early stages of L2 classroom learning.